Church and government in Reformed perspective - Dreyer, W. A. (HTS teologiese studies, 2005)
The new political dispensation since 1994 requires the Reformed churches in South Africa to redefine their role in society and their relationship with the government. This short journey through history helps us to understand the complexity of the relationship between the Church and the government. This article focuses on the concepts formulated by the Reformers in the 16th century, presenting the view that the revolutionary and radical way in which the Reformed concepts changed society and the government is still relevant to South Africa and opens up meaningful dialogue.